ADEQUACY AND RELEVANCE OF SOCIAL STUDIES CONTENT AND CURRICULUM RESOURCE MATERIALS IN FULFILLING THE OBJECTIVES OF CITIZENSHIP EDUCATION: THE CASE OF THREE UPPER PRIMARY SCHOOLS IN BOTSWANA. - Ezron, Mangwaya; Emily, Mangwaya (IJRDO- Journal of Educational Research, 2016)
Citizenship education is a relatively new phenomenon in developing countries in general andSouthern Africa in particular. Most southern African states teach citizenship educationthrough one or more subjects. In Botswana citizenship education is taught through SocialStudies. Where carrier subjects are used as a vehicle for teaching another subject challengesof balancing that subject’s content and the new subject are quite common. This studyexamines the adequacy and relevance of Social Studies content and resource materials infulfilling the objectives of citizenship education. This qualitative study used a case studydesign. Utilizing focus group interviews and observations the study established that whilecontent is generally adequate it does not take into account current Botswana contextualrealities. The study recommends interventions which could be made use of to ensure that thechanged Botswana social milleu is taken into account with respect to Social Studies contentand resource materials.